2008
DOI: 10.2165/00126839-200809040-00005
|View full text |Cite
|
Sign up to set email alerts
|

Aminaftone, a Derivative of??4-Aminobenzoic Acid, Downregulates??Endothelin-1 Production in??ECV304 Cells

Abstract: Aminaftone inhibits ET-1 production in cell cultures by interfering with transcription of the PPET-1 gene. These findings may account for the clinical efficacy of aminaftone in the treatment of capillary disorders and may encourage conduct of further clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…He was re-evaluated 2 months after discontinuation of the drug and, again, showed an increase in proteinuria (from 98.3mg/dL to 573mg/dL = +474.7mg/dL), substantially the same GFR and creatinine values, and a new increase in arterial blood pressure to 140/85mmHg: this kind of re-challenge clearly demonstrates the relationship between proteinuria and aminaphtone therapy. The recent preclinical findings about aminaphtone (anti-ET-1 and anti-E-selectin activities together with a significant endothelial antiphlogistic effect) [ 19 – 23 ] seem to correlate with this result, confirming that microangiopathy is the leading cause of microalbuminuria in patients with IDDM.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…He was re-evaluated 2 months after discontinuation of the drug and, again, showed an increase in proteinuria (from 98.3mg/dL to 573mg/dL = +474.7mg/dL), substantially the same GFR and creatinine values, and a new increase in arterial blood pressure to 140/85mmHg: this kind of re-challenge clearly demonstrates the relationship between proteinuria and aminaphtone therapy. The recent preclinical findings about aminaphtone (anti-ET-1 and anti-E-selectin activities together with a significant endothelial antiphlogistic effect) [ 19 – 23 ] seem to correlate with this result, confirming that microangiopathy is the leading cause of microalbuminuria in patients with IDDM.…”
Section: Discussionsupporting
confidence: 54%
“…Aminaphtone (2-hydroxy-3-methyl-1,4-napthohydroquinone-2-p-aminobenzoate) is a synthetic molecule derived from four aminobenzoic acids which is currently employed for “capillary disorders” and for chronic venous insufficiency [ 18 ]. This drug has recently demonstrated the ability to downregulate ET-1 production in ECV304 cells by interfering with transcription of preproET-1 (PPET-1) gene expression [ 19 ]. At the same time, cytofluorometry has shown that aminaphtone significantly reduces the expression of E-selectin (endothelial-leukocyte adhesion molecule 1; ELAM-1) both in resting and in ET-B -activated ECV304 cells in a dose-dependent manner [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another molecule, Aminaftone, compound 2-hydroxy-3-methyl1-1,4-napthohydroquinone-2-p-aminobe nzoatate (C18-H15-N-O4) used in the treatment of capillary disorders, has been reported to be effective in reducing vessel permeability and the number and size of leg ulcers in patients with chronic venous insufficiency [12,13,14]. Results from preliminary and open label studies suggested that the activity of aminaftone may be related to downregulation of ELAM-1 and VCAM-1 expression and to endothelium remodelling induced by down-regulates ET-1 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Scorza et al [80] analyzed the influence of aminaphtone, a 4-aminobenzoic acid derivative clinically used for the treatment of capillary disorders, on ET-1 protein production, pre pro endothelin (PPET-1) gene expression and ECE activity in human ECV304 cells after incubation with physiological concentrations of interleukin-1 β (IL-1 β ). ECV304 cells originate from endothelial cells of human umbilical vein by spontaneous transformation and have been widely used for in vitro studies of the endothelium and ET-1 pathways, since they are able to produce ET-1 and express the mRNA and the α -isoform of ECE.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that addition of different concentrations of aminaphtone to ECV304 cells reduces production of ET-1 and downregulates PPET-1 gene expression in a concentration-dependent manner. Moreover they observed that aminaphtone at a concentration of 6  μ g/mL, which roughly represents the peak plasma concentration reached after oral administration of 75 mg of the drug, reverts production of ET-1 to baseline values [80]. This may encourage clinical trials on the efficacy of this molecule in the downregulation of ET-1 levels in eye disorders.…”
Section: Discussionmentioning
confidence: 99%